2016
DOI: 10.1111/eea.12396
|View full text |Cite
|
Sign up to set email alerts
|

How predation by Podisus nigrispinus is influenced by developmental stage and density of its prey Alabama argillacea

Abstract: The functional response of a predator to the density of its prey is affected by several factors, including the prey's developmental stage. This study evaluated the functional response of Podisus nigrispinus (Dallas) (Hemiptera: Heteroptera: Pentatomidae) females to fourth instars and pupae of Alabama argillacea (H€ ubner) (Lepidoptera: Noctuidae), an important pest of cotton (Gossypium hirsutum L., Malvaceae) in Brazil. The prey were exposed to the predator for 12 and 24 h, and in densities of 1, 6, 12, 18, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
5
0
2
Order By: Relevance
“…Some larvae respond to predator attacks through natural, chemical, behavioral or physiological stimuli, and also by induction, with evasive or defense movements (Grosman et al, 2008;Greeney et al, 2009). Prey movements may also stimulate the attack and influence the predation activity and success (Zanuncio et al, 2008;Silva et al, 2012;Vacari et al, 2012;Santos et al, 2016), as observed in E. annulipes. However, other food resources may be present in the field and the predator may consequently show greater selection of food due to its omnivorous nature (Kocarek et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Some larvae respond to predator attacks through natural, chemical, behavioral or physiological stimuli, and also by induction, with evasive or defense movements (Grosman et al, 2008;Greeney et al, 2009). Prey movements may also stimulate the attack and influence the predation activity and success (Zanuncio et al, 2008;Silva et al, 2012;Vacari et al, 2012;Santos et al, 2016), as observed in E. annulipes. However, other food resources may be present in the field and the predator may consequently show greater selection of food due to its omnivorous nature (Kocarek et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Esta mortalidad se incrementó a un 73,51% deduciendo por diferencia que probablemente la liberación de C. valida puede llegar a ejercer hasta un control del 50%. La comprensión de la interacción de los depredadores y sus fuentes de alimentación ayuda a optimizar las estrategias de control biológico (Dos Santos et al, 2016).…”
Section: ) Depredación En Campo De C Valida Sobre D Citriunclassified
“…The preference behavior observed of the ringlegged earwig has previously been described for others, for instance, the feeding preference of the pentatomid Podisus nigrispinus (Dallas) for lepidopteran larvae over pupae in choice tests (Vacari et al, 2012;Santos et al, 2016). The preference behavior observed of the ringlegged earwig has previously been described for others, for instance, the feeding preference of the pentatomid Podisus nigrispinus (Dallas) for lepidopteran larvae over pupae in choice tests (Vacari et al, 2012;Santos et al, 2016).…”
Section: Discussionmentioning
confidence: 77%
“…The R 2 adj measured the strength of the relationship between the model and the predation data (Santos et al, 2016). L can be obtained using sample size (n) and residual sum of squares (RSS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation